The early Soviet period 1917-1929 - Gregor, Richard (Resolutions and decisions of the Communist Party of the Soviet Union ;, 1974)
This set of four volumes is an indispensable reference work for the study of modern Russia in general and Soviet Communism in particular. Volume 2 deals with the period from the October Revolution to the establishment of Stalin's regime.